Confined and Directed Polymer Crystallization at Curved Liquid/Liquid Interface. Issue 3 (29th December 2017) - Staub, Mark C.; Li, Christopher Y.
Abstract: Spherical crystals are ubiquitous in nature and the necessary breaks in translational symmetry not seen in flat crystals render them structurally unique. Polymer crystals have been shown to exhibit nonflat morphologies, but control over their formation is difficult to achieve. One strategy is directing the crystallization by spatially and/or temporally tuning chain segmental mobility. This has been studied early on using polymer blends or polymer/solvent systems where coupling liquid–liquid phase separation with crystallization could provide morphological control. In this Trend article, a recent trend in using miniemulsion systems to act as nanoscale confinement on chain segmental mobility is reviewed. The confinement at this length scale causes unique features to arise in ordering processes such as liquid–liquid phase separation and crystallization that are not observed at the macroscale. The generality of this approach makes it a good candidate to direct the formation of new and unique hierarchical polymer nanostructures that could be utilized in numerous applications. Abstract : Controlling ordering processes such as liquid‐liquid phase separation and crystallization in polymers under nanoscale confinement can produce unique and useful hierarchical nanostructures. A recent trend of using miniemulsion systems to confine polymer crystallization is reviewed. This system allows insight into fundamental polymer processes in nanoscale confinement along with promise for development of new polymer nanostructures for various applications.